Collectivist values help solve the climate dilemma - Pansini, Riccardo; Shi, Lei (Frontiers in Human Dynamics, 2025)
Theories on evolution of cooperation assume that interacting individuals can change their strategies under different expected payoffs and cultural contexts. The willingness to invest resources into partners and to cooperate may therefore vary in collectivistic Eastern Asia as opposed to more individualistic Western countries partly because of cultural differences. An experiment was implemented examining the willingness of young Chinese subjects to mitigate the consequences of climate change in a country severely affected by air pollution. We set up a public goods game in which groups of six students had to reach a minimum investment threshold to be able to save funds for a reforestation project to curb climate change. Such social dilemma could not be solved in the western world. Here, instead, five out of eight Chinese groups cooperate enough to raise funds for the reforestation goal. An Individualism/Collectivism questionnaire we presented the subjects with established why we are confronted with a variance in cooperation interests across different cultures. In China, in fact, collectivistic values seem to be a key factor for allowing the emergence of this environmentally driven cooperation.